Reexamination of the crustal boundary context of Mesoproterozoic granites in southern Nevada using U-Pb zircon chronology and Nd and Pb isotopic compositions - Almeida, Rafael V. (2019)
Granites crystallize from melts with a range of compositions and textures that provide important clues about the evolution of the continental crust. Rapakivi or A-type granites are usually inferred to be unrelated to active tectonic processes. Granites that fall into this category are widespread across the interior of North America. They are generally considered to be 1450–1400 Ma and anorogenic. We report new and substantially older U-Pb zircon ages of 1683.2 ± 4.7, 1681.4 ± 5.1, and 1683.3 ± 6.1 Ma for rapakivi granites from the Davis Dam area, the Lucy Gray Range, and the Newberry Mountains of southern Nevada, respectively. These granites are thus associated with the Ivanpah orogeny. Rapakivi granites from Gold Butte, Nevada, also previously thought to be 1450–1400 Ma, yielded a younger U-Pb zircon age of 1373 ± 23 Ma. In addition to these new age constraints, new Nd and Pb isotope data allow us to refine previously mapped isotopic crustal boundaries. Nd and Pb isotopes from the ~1680 Ma granites indicate a brief residence in the crust prior to crystallization, whereas the source of the younger Gold Butte granite appears to have significant crustal heritage. The modified isotopic province boundaries are now more consistent with each other than in earlier interpretations, a result that reinforces the view that these boundaries reflect fundamental tectonic features related to Paleoproterozoic crustal accretion. Our data imply that the spatial distribution of the classic anorogenic granite suite in North America is more restricted than previously thought. They also draw attention to the need for more extensive dating and radiogenic isotope measurements to probe the midcontinent belt of granites more broadly. Although plutons look alike, it can no longer be assumed that they were intruded synchronously or formed from the same source.